Treatment of blunt splenic injury in children in China - Wang, Wu; Lei, Haiyan; Zhang, Wenhan; Li, Wenhai; Bian, Hongqiang; Yang, Jun (Frontiers in Surgery, 2024)
IntroductionNonoperative management (NOM) is recognized as a viable treatment for pediatric closed splenic trauma. However, clinical guidelines are applied inconsistently, resulting in different treatment strategies in different regions. This study aimed to investigate the independent risk factors influencing the length of stay in pediatric closed splenic injuries and to analyze the key determinants in the choice of surgical treatment to optimize inpatient management and patient care and improve outcomes.MethodsA retrospective evaluation of medical records of pediatric patients with blunt splenic injury (BSI) admitted to Wuhan Children's Hospital from 2020 to 2024 was conducted. The dataset included demographics, mechanism of injury, injury grade, associated injuries, therapeutic measures, and outcomes, which were subjected to statistical analysis. Factors influencing length of hospital stay and treatment regimen were also analyzed.ResultsA total of 88.5% of patients underwent NOM, with 11% requiring splenic embolization due to hemodynamic instability or arterial hemorrhage. Surgery was required in 11.5% of patients, primarily for combined gastrointestinal perforation, or peritonitis. One patient died due to brain injury. Trauma scores and transfusion requirements were higher in the surgical group (37.7 ± 16.1 vs. 17.2 ± 13.1, p < 0.001; 21.7% vs. 100%, p < 0.001). Multivariate logistic regression showed that gastrointestinal complications significantly influenced the decision to operate (p = 0.0087). A generalized additive model showed a corresponding increase in length of stay with increasing injury severity, with the curve flattening in the mid to high ISS range (40–60).ConclusionNOM remains an effective and preferred treatment strategy for pediatric BSI, particularly in the setting of stable hemodynamic parameters. This approach reduces the need for surgical intervention and associated complications while preserving splenic function. The study highlights that gastrointestinal complications are important determinants of surgical management. Further research into long-term outcomes and advancements in conservative management are needed.